Poppy and Rye - Avi, 1937-; Floca, Brian (New York : Avon, 1998)
When their home next to a brook is destroyed by beavers, a large family of golden mice is aided by Poppy the deer mouse and her grumpy porcupine friend, who in the process forges a relationship with the son he had abandoned.
Wilson's Children.
Elem. School Library Collection.
Publisher's Weekly.
4.3
3-6
620L
Keywords: Mice -- Fiction; Porcupines -- Fiction; Animals -- Fiction; Fathers and sons -- Fiction; Mice -- Fiction; Porcupines -- Fiction; Father-son relationship -- Fiction; Fathers and sons -- Fiction